AN ANALYSIS OF ANTHOLOGY POETRY STRUCTURE OF NETRA CINTA BY SELAWITRI - Mumin Fakot; Rochmat Tri Sudrajat (IKIP Siliwangi, 2021)
This study aims to determine the physical structure and inner structure in the anthology of Netra Cintapoetries. Based on the research problems, this research aims to describe the morals contained in the Netra Cintapoetrycollections. The method applied in this study was qualitative research methods as descriptive analysis design. The writer used this method because the writer tried to know and describe the physical structure, inner structure and description of morality in the anthology of Netra Cinta poetrywhich is the object of this research. The research instrument was the documentation technique. The using of this documentation technique is done by reading poetry data sources which aimsto identify data in accordance with the theory used. After obtaining this research data, further analysis of the research data is carried out with content analysis techniques. The process of data analysis could be done by mastering the physical and inner elements as well as the moral description contained in the poetry anthology of Netra Cinta. The results showed that the physical structure in the anthology of Netra Cinta poetry used diction and concrete words that are disappointed. Anthology of Netra Cinta poetry typifies in straight stanzas. The dominant inner structure is the expression of feelings in the soul. The feeling depicted is a feeling of disappointment, sadness, pride and anger towards the state of the animal who is not good at taking advantage of opportunities.